2004
DOI: 10.1038/sj.bjc.6601775
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between 3p deletions and telomerase activity in non-small-cell lung cancer: prognostic implications

Abstract: 3p deletions and telomerase reactivation are two of the most frequent events described in relation to non-small-cell lung cancer (NSCLC) pathogenesis. Moreover, a number of genes that map on 3p have been proposed as candidates to tumour-suppressor genes of importance in the lung cancer process. In this work, we analysed deletions at different 3p loci in relationship to telomerase activity in 66 NSCLCs obtained from patients who had suffered potentially curative surgery. Also, we evaluated prognostic implicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…Both genes map in 3p (3p21.31-p21.1 and 3p21.3, respectively), and chromosome 3p deletions constitute one of the most frequent events described in relation to NSCLC pathogenesis. Previous data from our group and others [33] suggested the existence on 3p of one or several genes implicated on telomerase negative regulation.…”
Section: Discussionmentioning
confidence: 54%
“…Both genes map in 3p (3p21.31-p21.1 and 3p21.3, respectively), and chromosome 3p deletions constitute one of the most frequent events described in relation to NSCLC pathogenesis. Previous data from our group and others [33] suggested the existence on 3p of one or several genes implicated on telomerase negative regulation.…”
Section: Discussionmentioning
confidence: 54%
“…This reactivation seems to arrest the normal loss of telomeric DNA incurred as somatic cells divide. Since continual loss of telomeric DNA is predicted to eventually limit cell proliferation, activation of telomerase in cancer cells may be an important step in the acquisition of cell immortalisation, which occurs during tumor progression [5].…”
Section: Introductionmentioning
confidence: 99%
“…Iniesta et al found correlation between telomerase activity and loss of heterozygosity at position 3p14.3 [224]. Deletion at this position was also associated with poor prognosis.…”
Section: Chromosomementioning
confidence: 98%